Sports Media : Reporting, Producing and Planning - Schultz, Brad, 1961-; Arke, Ed (Focal Press, 2016)
Sports Media covers reporting, anchoring, and production, and offers thorough descriptions of the sports reporter and anchor's function in sports journalism. This text offers important historical background on the evolution of the sports industry, some grounding in the business of sports, and a discussion of social issues including the experience of women in sports journalism